Master slave husband wife : an epic journey from slavery to freedom [compact disc, unabridged] - Woo, Ilyon (Simon & Schuster Audio, 2023)
The remarkable true story of Ellen and William Craft, who escaped slavery through daring, determination, and disguise, with Ellen passing as a wealthy, disabled white man and William posing as 'his' slave.